2002
DOI: 10.1186/gb-2002-3-7-reviews3009
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An emerging family of structurally distinct dual-specificity serine, threonine and tyrosine phosphatases that act on MAP kinases consists of ten members in mammals, and members have been found in animals, plants and yeast. Three subgroups have been identified that differ in exon structure, sequence and substrate specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(109 citation statements)
references
References 69 publications
2
105
1
1
Order By: Relevance
“…2,3 Also known as mitogenactivated protein kinase phosphatase 3 (MKP3), DUSP6 additionally plays a key role in regulating extracellular signal-regulated kinase (ERK) 1/2 pathway which is implicated in pathophysiology of major psychiatric disorders. 4,5 Although Toyota et al (2000) reported a lack of association between Japanese bipolar patients and T/G polymorphism (rs2279574, Leu114Val) in DUSP6 gene, 6 a number of recent findings strongly suggests the involvement of DUSP6 in mediating psychiatric manifestations. For example, DUSP6 mRNA increases after electroconvulsive seizure in rat brain.…”
mentioning
confidence: 99%
“…2,3 Also known as mitogenactivated protein kinase phosphatase 3 (MKP3), DUSP6 additionally plays a key role in regulating extracellular signal-regulated kinase (ERK) 1/2 pathway which is implicated in pathophysiology of major psychiatric disorders. 4,5 Although Toyota et al (2000) reported a lack of association between Japanese bipolar patients and T/G polymorphism (rs2279574, Leu114Val) in DUSP6 gene, 6 a number of recent findings strongly suggests the involvement of DUSP6 in mediating psychiatric manifestations. For example, DUSP6 mRNA increases after electroconvulsive seizure in rat brain.…”
mentioning
confidence: 99%
“…Dual specificity (Thr/Tyr) protein phosphatases play an important role in the regulation of signaling by mitogen-activated protein (MAP) 1 kinases in eukaryotic cells (1)(2)(3). These MAP kinase phosphatases (MKPs) act in direct opposition to the MAP kinase kinases (MKKs or MEKs) to dephosphorylate and inactivate the MAP kinase, thus regulating the duration and magnitude of activation and hence the biological outcome of signaling.…”
mentioning
confidence: 99%
“…There are 10 distinct MKPs in mammalian cells (3), and these enzymes feature a common structure comprising a carboxyl-terminal catalytic domain with sequence similarity to the prototypic VH1 dual specificity phosphatase of vaccinia virus (8) and an amino-terminal noncatalytic domain containing two short regions of homology with the cell cycle regulatory phosphatase cdc25 (9). MKPs can be subdivided into three main groups based on sequence similarity, gene regulation, and subcellular localization (1)(2)(3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The classic MKPs are a family of ten dual specificity threonine/tyrosine phosphatases that differ in tissue distribution, MAP kinase specificity, and subcellular distribution (41). Some MKPs are exclusively nuclear, others localize to the cytosol or shuttle between nucleus and cytosol.…”
Section: Erk1/2 Activated By Nk1-␤-arrestin1 Is Less Susceptible To Dmentioning
confidence: 99%